1998
DOI: 10.1046/j.1525-1594.1998.06137.x
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Nonpulsatile Left Heart Bypass with Reduced Systemic Pulse Pressure Causes Morphological Changes in the Aortic Wall

Abstract: We investigated the morphological changes in the aorta due to reduced systemic pulse pressure in prolonged nonpulsatile left heart bypass (LHB). Nineteen adult goats were divided into 3 groups, the nonpulsatile group in which nonpulsatile LHB was conducted, the pulsatile group in which pulsatile LHB was conducted, and the control group used as the normal control. The average aortic pulse pressures were 12, 47, and 37 mm Hg, respectively. The descending aorta was subjected to morphological examination. In the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 19 publications
0
35
0
1
Order By: Relevance
“…Although NOSE (1993) reported that a long-term non-pulsatile biventricular bypass did not produce harmful physiological effects in animals, recent studies have suggested that a prolonged non-pulsatile left heart bypass can produce certain effects on the arterial structure and function, such as the wall thickness, smooth muscles and vasoconstrictive function of the vessels (NISHIMURA et al, 1998;NISHINAKA et al, 2001).…”
Section: Comparisons O F Synchronous and Non-synchronous Operations Omentioning
confidence: 99%
“…Although NOSE (1993) reported that a long-term non-pulsatile biventricular bypass did not produce harmful physiological effects in animals, recent studies have suggested that a prolonged non-pulsatile left heart bypass can produce certain effects on the arterial structure and function, such as the wall thickness, smooth muscles and vasoconstrictive function of the vessels (NISHIMURA et al, 1998;NISHINAKA et al, 2001).…”
Section: Comparisons O F Synchronous and Non-synchronous Operations Omentioning
confidence: 99%
“…In this study the pulse pressure was reduced to about 10mmHg, which we considered a clinically available level. Furthermore, although the purpose of this study was to investigate changes in vascular control status that were possibly affected by atrophic changes in the arterial systems accompanying reduced pulse pressure, Nishimura et al [4][5][6] reported that atrophic changes in the arterial system were observed with a pulse pressure of about 10mmHg.…”
Section: Discussionmentioning
confidence: 97%
“…The influences of reduced systemic pulse pressure have been investigated in nonpulsatile left heart bypass (NLHB). Nishimura et al [4][5][6] reported morphological changes in the arterial system caused by prolonged NLHB in a chronic animal study. There was an increase in the ratio of elastin, a decrease in arterial wall thickness, and atrophy of smooth muscle cells.…”
Section: Introductionmentioning
confidence: 99%
“…As a natural left ventricle is a pulsatile pump, the long-term effects of a non-pulsatile pump have been an issue of considerable debate (NISHIMURA et al, 1998;LOEBE et al, 2001). …”
Section: Discussionmentioning
confidence: 99%